KELAYAKAN USAHA PEMBIBITAN KELAPA SAWIT BERSERTIFIKAT DI NAGAN RAYA, ACEH : LANGKAH AWAL MENINGKATKAN PENDAPATAN PERKEBUNAN RAKYAT - Yoga Nugroho (Jurnal Bisnis Tani, 2018)
The main purpose of this study were (1) to analyze the non-financial and (2) the financial feasibility of palm oil superior seed nursery in Nagan Raya, Aceh Province, and also (3) to identifiying the role of that nursery in order to increasing palm oil farmers income in west and south aceh area. Feasibility investment creteria, such as Net Present Value, Internal Rate of Return, Net Benefit per Cost Ratio, and Discounted Payback Period were use in financial feasibility analysis. The findings of this study showed that (1) the palm oil superior seed nursery in Nagan Raya, Aceh province were non-financially feasible in consideration of strategic location, soldout product, and experienced labor. (2) The NPV Value were greater than zero (Rp 341.372.170,-) showed that this nursery also financially feasible.  (3) The use of superior seed from nursery’s production should increasing palm oil productivity and also will increasing farmers income in west and south aceh area.